Tert‐Butyl Sulfoxides: Key Precursors for Palladium‐Catalyzed Arylation of Sulfenate Salts. Issue 9 (15th June 2015) - Gelat, Fabien; Lohier, Jean‐François; Gaumont, Annie‐Claude; Perrio, Stéphane
Abstract The present report describes an efficient and clean generation of sulfenate salts (R1SO−) by pyrolysis of readily available tert‐butyl sulfoxides to give sulfenic acids (R1SOH) and traceless isobutene, followed by hydrogen abstraction with a weak inorganic base (K3PO4). The relevance of this process was exemplified through an in situ palladium‐catalyzed cross‐coupling reaction with aryl halides/triflates leading to aryl sulfoxides. The operationally simple CS bond‐forming protocol developed uses Pd(dba)2 as catalyst and Xantphos as ligand in toluene or a toluene/H2O mixture. Further extensions include the use of di‐tert‐butyl sulfoxide as an equivalent for sulfur monoxide dianion (SO2−) and the development of diastereoselective versions in the [2.2]paracyclophane and biaryl series.